About a boundary value problem for the loaded equation of mixed type - Ramazanov, M.I.; Zhanbolova, A.K. (Ye.A.Buketov Karaganda State University Publishing house, 2014)
Boundary value problem for the loaded equation of mixed type in a rectangular domain is investigated. Feature of the problem is that you can not directly invert the operator of the hyperbolic and elliptic parts and reduce the initial problem to the study of the solvability of singular integral equations. Conditions of existence of a unique 2 L — strong solution are found.
Аралас типті жүктеулі теңдеу үшін берілген бір шеттік есеп туралы
Об одной краевой задаче для нагруженного уравнения смешанного типа
Keywords: loaded equations; equations of mixed type; L -strong solution; boundary value problem for a loaded equation